REMOVAL OF LEAD FROM INDUSTRIAL WASTEWATER BY ELECTROCOAGULATION USING SACRIFICIAL ALUMINIUM ELECTRODES - FOGARASI, Szabolcs; IMRE-LUCACI, Florica; GHIRIŞAN (MICLĂUȘ), Adina; MIȘCA, Barbu Radu Horațiu; IMRE-LUCACI, Árpád (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The aim of this study was to develop an ecological method for the removal of Pb2+ ions from industrial wastewater. The electrocoagulation (EC) process of Pb2+ has been studied, using an electrolytic flow cell (flow rate of 20, 40, 60 mL/min) equipped with sacrificial Al electrodes, operated under galvanostatic mode (current density of 5, 10 and 15 mA/cm2). In all experimental conditions the concentration of Pb2+ was lowered below the maximum allowable concentration (0.5 ppm). The experimental results showed that the performances of the process are more strongly dependent on the applied current density than on the applied flow rate. The electrolytic flow cell has proved to be quite effective, allowing the complete removal of lead with a specific energy consumption of 3.08 kWh/kg Pb removed.